Efektivitas Produk Herbal Antijamur untuk Terapi Ketombe (Pityarisis capitis): Literature Review dan Analisis Bibliometrik - Esti Syahrin; Hadi Sudarjat; Rachel Noveriachristie Balapadang (Poltekkes Kemenkes Padang, 2025)
Dandruff (Pityriasis capitis) is a skin health problem caused by fungal growth on the scalp, increased production of oil glands (sebum) excessively. Current advances in science and technology have led to the development of herbal plant research to be used as antifungal herbal products in overcoming dandruff. The purpose of this literature review is to review and summarize herbal plants that have the potential to inhibit the growth of fungi that cause dandruff, so that it is useful to be developed as further research. Article searches were conducted from February to May 2024 using the Publish or Perish reference manager (PoP) tool in the Google scholar database source which was then term mapped in the Vosviewer software. The results of original research journal publications related to dandruff published in the range of 2014 to 2024 were obtained as many as 12 journals. The conclusion obtained in this literature review is that secondary metabolite compounds contained in herbal plants have a potential fungal inhibition mechanism, so it is appropriate to be developed in future research and used as an antifungal herbal product to treat dandruff.